LATE QUATERNARY ICE-RICH PERMAFROST SEQUENCES AS A PALEOENVIRONMENTAL ARCHIVE FOR THE LAPTVE SEA REGION IN NORTHERN SIBERIA - Schirrmeister L.; Siegert C.; Kunitzky V.V.; Grootes P.M.; Erlenkeuser H. (My University, 2002)
Ice-rich permafrost sequences with large polygonal ice wedges represent excellent archives for paleoenvironmental reconstruction. Such deposits contain numerous well-preserved records (ground ice, paleosols, peat beds, different types of fossils), which permit characterization of environmental conditions during a clearly defined period of the past 60 ka. Based on field investigations carried out within framework of the German-Russian project "Laptev Sea System 2000" on the Bykovsky Peninsula (SE of the Lena Delta) results from cryolithological studies, sedimentological analyses, as well as new radiocarbon data are presented. For the first time it is shown that the Ice Complex accumulated without significant interruptions from approximately 60 k.y. B.P. until the end of the Pleistocene. Geochemical data (total organic carbon, C/N, δ13Corg) and the mass-specific magnetic susceptibility clearly show changing environmental conditions from stadial to interstadial times in the Late Pleistocene and during the transition to the Holocene. These results permit us to reconstruct the development of an Arctic periglacial landscape in the coastal lowland during Ice Complex formation in the Late Quaternary. This evolution coincided generally with the global environmental trend up to marine isotope stage 4.
Keywords: Paleoenvironment; Permafrost deposits; Peat; Thermokarst; Siberian Arctic; Laptev Sea; Radiocarbon dating; Late Quaternary; Cenozoic::Quaternary; Кайнозой::Четвертичная